PENGEMBANGAN KEMAMPUANSISWA MENELITI SEJARAH LOKAL MELALUI MODEL INKUIRI (Studi Kasus di SMA Negeri 5 Purwokerto) - Suwamo Suwamo; Kartono Kartono (LPMPP Universitas Negeri Yogyakarta, 2007)
Thepurpose of this study is know effectivity of inquiry's model in developingpupil's ability studying local history at SMA Negeri 5 Purwokerto year of 20062007. This study is a classroom action research with subject mailer of history andtopic about principles historical research. There are four phase in this classroomactiOn research, i.e.: planning, classroom action, observationand reflection.The result of thisstudy shows that inquiry'S model effective enough todevelopingpupil's ability in studying local history. There is significant improvingin instructional process of historical subject matter by inquiry's model from firstcydies toward third cyclies. The significan, improving could be seen by pretest andPOSllest values in every cyclies, angket value in first cyclies, and collective's dutiesfrom first cyclies toward third cyclies